"Effect of prying forces and contact stresses on steel joint components subjected to tension" - ساحللي, سامر (Latakia University Journal -Engineering Sciences Series, 2025)
Hanger connections are important steel connections in which bolts and/or welding are used to connect steel plates together. They are similar, according to many references, to what is called the Equivalent T-stub. they are found in most connections, for example, connections using partial end plates. Like other types of connections, they are subjected to different types of forces and stresses in their components depending on the design forces transmitted between the connected elements. One of the main challenges when transferring tensile forces in these connections is the emergence of lifting or prying forces that negatively affect the bolts by increasing the contact stresses between the connected plates, which may lead to deformation of the plates near the bolts. These deformations, whether in the form of bending or rotation, may cause increasing the design axial loads of the bolts, affecting the strength of the connection and increasing the risk of premature failure. In this research paper, the differences in the methods of calculating additional tensile forces (prying forces) and their results according to some references will be highlighted, in addition to helping in understanding how they develop and the effect of the most important factors on them, such as the thickness of the front plate, the diameters of the bolts, bolts grade, and the way they are distributed (the spacing between them) through comparison with a parametric analytical study using the component-based finite element method (CBFEM) for a beam-column with partial end plate bolted connection.